Does Gender-Fair Language Pay Off? The Social Perception of Professions from a Cross-Linguistic Perspective - Horvath, Lisa K.; Merkel, Elisa F.; Maass, Anne; Sczesny, Sabine (Frontiers in Psychology, 2016)
In many languages, masculine forms (e.g., German Lehrer, ‘teachers, masc.’) have traditionally been used to refer to both women and men, although feminine forms are available, too. Feminine-masculine word pairs (e.g., German Lehrerinnen und Lehrer, ‘teachers, fem. and teachers, masc.’) are recommended as gender-fair alternatives. A large body of empirical research documents that the use of gender-fair forms instead of masculine forms has a substantial impact on mental representations. Masculine forms activate more male representations even when used in a generic sense, whereas word pairs (e.g., German Lehrerinnen und Lehrer, ‘teachers, fem. and teachers, masc.’) lead to a higher cognitive inclusion of women (i.e., visibility of women). Some recent studies, however, have also shown that in a professional context word pairs may be associated with lesser status. The present research is the first to investigate both effects within a single paradigm. A cross-linguistic (Italian and German) study with 391 participants shows that word pairs help to avoid a male bias in the gender-typing of professions and increase women’s visibility; at the same time, they decrease the estimated salaries of typically feminine professions (but do not affect perceived social status or competence). This potential payoff has implications for language policies aiming at gender-fairness.